2023
DOI: 10.1021/acs.jpcb.2c07568
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insights into the Inhibitory Mechanism of Tyrosine Phosphorylation against the Aggregation of Human Tau Fragment PHF6

Abstract: Abnormal aggregation of the microtubule-associated protein tau into intracellular fibrillary inclusions is characterized as the hallmark of tauopathies, including Alzheimer’s disease and chronic traumatic encephalopathy. The hexapeptide 306VQIVYK311 (PHF6) of R3 plays an important role in the aggregation of tau. Recent experimental studies reported that phosphorylation of residue tyrosine 310 (Y310) could decrease the propensity of PHF6 to form fibrils and inhibit tau aggregation. However, the underlying inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 75 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…A number of computational and experimental studies have manifested the crucial role of Y310 in the tau aggregation, as Y310 could form CH−π interactions with residue I308 and display π−π interaction with itself. 39,41,45,46 Therefore, we further examined whether NQDA interferes with these CH−π and π−π interactions. The PDFs of intra-chain and inter-chain CH−π distance between the atom Cγ of I308 and the benzene ring of Y310 are shown in Figure S8.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of computational and experimental studies have manifested the crucial role of Y310 in the tau aggregation, as Y310 could form CH−π interactions with residue I308 and display π−π interaction with itself. 39,41,45,46 Therefore, we further examined whether NQDA interferes with these CH−π and π−π interactions. The PDFs of intra-chain and inter-chain CH−π distance between the atom Cγ of I308 and the benzene ring of Y310 are shown in Figure S8.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…H-bonding interactions are considered to be crucial to the fibrillization of tau peptide fragments. ,, Therefore, we calculated the PDFs of the total H-bond number of PHF6* and PHF6 in four systems. As seen in Figure a, the PDF curve of the H-bond number presents the peak at the number of 56 in the PHF6* system, and the notable peak shift toward a small number is observed in the NQDA-PHF6* system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, fragments of the Tau protein containing R3 may be originated within the human brain by endopeptidase cleavage and these fragments may be crucial in amyloid core formation. Specifically, the hexapeptide VQIVYK (paired helical filament 6, PHF6), located in R3, is considered crucial for Tau fibrillation. Cryo-EM analysis of Tau filaments isolated from Alzheimer’s patients has revealed that the PHF6 sequence constitutes the first β-strand of the filament core . Cross-linking mass spectrometry, recombinant protein and synthetic peptide systems, in silico modeling and cell models have additionally shown that the PHF6 motif forms metastable compact structures with its upstream sequence that modulate aggregation propensity …”
Section: Introductionmentioning
confidence: 99%